Improved indoor air temperature and humidity control using a novel direct-expansion-based air conditioning system. (November 2021) - Yang, Liu; Deng, Shiming; Fang, Guanyu; Li, Weilin
Abstract: Many approaches have been tried to obtain an improved indoor thermal environment in small-to medium-sized buildings located in hot-humid climates when using direct-expansion (DX)-based air conditioning (A/C) systems. However, inadequacies still existed in these approaches. Therefore, to address these problems, a novel DX-based A/C system with a two sectioned cooling coil (TS-DXAC) has been proposed. In this paper, a control strategy to operate the TS-DXAC system for achieving an improved indoor air temperature and humidity control in hot and humid climates is presented. Firstly, the detailed configurations of the TS-DXAC system and the control strategy of the TS-DXAC system are presented. The developed strategy included two control algorithms, i.e., Algorithm I and Algorithm II, enabling the TS-DXAC system to be operated under two different indoor conditions, i.e., hot-humid, and hot-dry, respectively. Secondly, a test TS-DXAC system was set up and the controllability tests for the control strategy were carried out. This is followed by presenting the experimental results and related discussions. The experimental results demonstrated that in all the tests, indoor air temperature could be directly controlled at the two indoor conditions, while indoor air temperature and relative humidity could be simultaneously controlled over a relatively long period at a hot-humid indoor condition using Algorithm I. The control strategy enabled the TS-DXAC system to respond the changes in either indoor settings or cooling loads by outputting variable sensible and latent cooling capacities at a higher energy efficiency compared to conventional On-Off controlled DX A/C systems. However, to improve the control sensitivity under Algorithm I, consideration should be given to the variable speed operation of the compressor in the TS-DXAC system. Highlights: A novel two sectioned direct expansion A/C (TS-DXAC) system was proposed. A control strategy to operate the TS-DXAC system has been developed. It enabled the TS-DXAC system to be operated in hot and humid climates. Improved indoor thermal control and better air distribution can be achieved.